2011
DOI: 10.1117/12.881713
|View full text |Cite
|
Sign up to set email alerts
|

Shadowing effect modeling and compensation for EUV lithography

Abstract: Extreme ultraviolet (EUV) lithography is one of the leading technologies for 16nm and smaller node device patterning. One patterning issue intrinsic to EUV lithography is the shadowing effect due to oblique illumination at the mask and mask absorber thickness. This effect can cause CD errors up to a few nanometers, consequently needs to be accounted for in OPC modeling and compensated accordingly in mask synthesis. Because of the dependence on the reticle field coordinates, shadowing effect is very different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 2 publications
(5 reference statements)
0
14
0
Order By: Relevance
“…For the flare effect, OPC corrects the CD of a layout pattern according to the flare value the pattern receives [35,41]. For the shadowing effect, OPC modifies each layout pattern according to the pattern shape and the pattern location [26,33]. However, these two effects should be simultaneously considered since they might conflict with each other, reducing OPC efforts.…”
Section: Simultaneous Shadowing and Flare Compensation With Opcmentioning
confidence: 97%
See 2 more Smart Citations
“…For the flare effect, OPC corrects the CD of a layout pattern according to the flare value the pattern receives [35,41]. For the shadowing effect, OPC modifies each layout pattern according to the pattern shape and the pattern location [26,33]. However, these two effects should be simultaneously considered since they might conflict with each other, reducing OPC efforts.…”
Section: Simultaneous Shadowing and Flare Compensation With Opcmentioning
confidence: 97%
“…It can be observed that horizontal 1-D equal L/S patterns of 30 nm pitch (P30H) suffer from rather high contrast loss compared to P60H. To compensate the shadowing effect in advanced process nodes, therefore, recent studies mainly focus on developing model-based OPC techniques [26,28,33]. Different shadowing models and lithography simulators adopted in these model-based OPC flows present a trade-off between runtime efficiency and correction effectiveness.…”
Section: Shadowing Effectmentioning
confidence: 98%
See 1 more Smart Citation
“…[6]. Figure 2(a) illustrates the sketch of the mask shadowing effect, where the outer and inner contours represent the target on the wafer scale and the print image due to the shadowing effect.…”
Section: Modeling Of the Mask Shadowing Effectmentioning
confidence: 99%
“…Both the absorber thickness, which is large compared to the wavelength, and the oblique incidence contribute to a pronounced shadowing and other mask topography effects [5]. The mask shadowing effect is orientation-dependent relying on the mask topography, which induces a directional CD bias and shift on the order of several nanometers [5,6]. In contrast with a 22-nm or smaller half-pitch, the mask shadowing effect is too pronounced to be ignored and must be compensated.…”
Section: Introductionmentioning
confidence: 95%